2012
DOI: 10.1128/jvi.06075-11
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Massive Virus-Specific Plasmablast Responses during Acute Dengue Virus Infection in Humans

Abstract: h Humoral immune responses are thought to play a major role in dengue virus-induced immunopathology; however, little is known about the plasmablasts producing these antibodies during an ongoing infection. Herein we present an analysis of plasmablast responses in patients with acute dengue virus infection. We found very potent plasmablast responses that often increased more than 1,000-fold over the baseline levels in healthy volunteers. In many patients, these responses made up as much 30% of the peripheral lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

45
273
7
18

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(343 citation statements)
references
References 33 publications
45
273
7
18
Order By: Relevance
“…Previous observations by our group (28,40) and others (51)(52)(53)(54) found that secondary immune responses show a characteristic appearance of Ag-specific plasmablasts in the PB between days 6 and 7, in contrast to the appearance of such cells after day 10 in response to primary immunization (55). Consistent with the characteristics of a secondary response, we detected an increased anti-TT IgG titer together with TT + PC and TT + mBC expansion at day 7 and found TT + PC declined by day 14, comparably between HD, splenectomized, and tonsillectomized individuals.…”
Section: Discussionmentioning
confidence: 65%
“…Previous observations by our group (28,40) and others (51)(52)(53)(54) found that secondary immune responses show a characteristic appearance of Ag-specific plasmablasts in the PB between days 6 and 7, in contrast to the appearance of such cells after day 10 in response to primary immunization (55). Consistent with the characteristics of a secondary response, we detected an increased anti-TT IgG titer together with TT + PC and TT + mBC expansion at day 7 and found TT + PC declined by day 14, comparably between HD, splenectomized, and tonsillectomized individuals.…”
Section: Discussionmentioning
confidence: 65%
“…Similarly, using B-cell ELISpots, antigen-specific ASCs against RSV were shown to arise after Day 17 and peak around Day 110 ( Figure 3A). Peak virus-specific ASC frequencies ranged from 5% to 50% of total ASCs, comparable with that after influenza or yellow fever vaccination ( Figure 3B) (30)(31)(32)(33). Thus, the virus-specific acute ASC responses to RSV infection appeared quantitatively intact.…”
Section: Induction Of Higher Plasmablast Frequencies Correlates Withmentioning
confidence: 61%
“…During secondary infection, large numbers of PBs are observed 6-7 d after the onset of fever (6,17); yet, the specificity of these PBs and their origin from either naive or MBCs has not been studied. PBs (CD20…”
mentioning
confidence: 99%